2023
DOI: 10.5334/pb.1171
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Compliance with Sanitary Behaviors among Students in Higher Education During the Second COVID-19 Wave: The Role of Health Anxiety and Risk Perception

Abstract: To limit the spread of COVID-19, public authorities have recommended sanitary behaviors such as handwashing, mask-wearing, physical distancing, and social distancing. We recruited a large sample of higher education students in Belgium (N = 3201-3441) to investigate the role of sociodemographic variables, mental health, previous COVID-19 infections, academic involvement, and risk perception on adherence to these sanitary behaviors. This cross-sectional study took place during the second COVID-19 wave in Belgium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Therefore, the author suggested that informing people of the hazardous risks and complications of COVID-19 could be an effective intervention to ensure that a high level of compliance remained. Another study, predicting compliance to COVID-19 sanitary measures (handwashing, mask-wearing, physical distancing, and social distancing), found that persons who were living alone, female gender, later in the academic curriculum, having higher general and health anxiety, higher academic involvement, and higher risk perception were positively associated with adherence to the COVID-19 measures mentioned earlier [78]. An Indonesian study with 461 adults looked at social determinants of COVID-19 protocol adherence and reported gender, age, educational level, economics, and social status were determinants of health protocol adherence [79].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, the author suggested that informing people of the hazardous risks and complications of COVID-19 could be an effective intervention to ensure that a high level of compliance remained. Another study, predicting compliance to COVID-19 sanitary measures (handwashing, mask-wearing, physical distancing, and social distancing), found that persons who were living alone, female gender, later in the academic curriculum, having higher general and health anxiety, higher academic involvement, and higher risk perception were positively associated with adherence to the COVID-19 measures mentioned earlier [78]. An Indonesian study with 461 adults looked at social determinants of COVID-19 protocol adherence and reported gender, age, educational level, economics, and social status were determinants of health protocol adherence [79].…”
Section: Discussionmentioning
confidence: 95%
“…There have been a number of research focusing on adherence to and compliance with COVID-19 measures. One is a notable study in Belgium with a sample of 2008 participants [78]. The study found that the measure of wearing a face mask while restricting their social bubble (to five people or less) was the one that was being followed least.…”
Section: Discussionmentioning
confidence: 99%
“…They also indicated that people have low perceptions of control over the COVID-19 pandemic. Studies show that the risk perception of the COVID-19 and worry about this pandemic are high among HCWs (Abdel Wahed et al, 2020; Abolfotouh et al, 2020; Batu et al, 2021; Dekeyser et al, 2023; Gorini et al, 2020; Le et al, 2021; Özer et al, 2023; Puci et al, 2020). These studies determined that the perception that the COVID-19 pandemic is long-lasting and that personal hygiene is important in the pandemic process in actively working HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…Various healthcare organizations organized online lectures and workshops for physicians, pharmacists, and healthcare workers to set up a constructive dialogue about people's vaccination intentions or the lack thereof, grounded in empirical work (Morbée, Vansteenkiste, et al., 2022). The collected findings also helped to set priorities by indicating the subgroups that were suffering most (e.g., young adults and in particular students in early 2021) and prompted actions of institutions for higher education to support the well‐being of students (see also Dekeyser et al., 2023; Schmits et al., 2021).…”
Section: Part 3: Societal Role Of the Motivation Barometermentioning
confidence: 99%